The most common health behaviors among patients with cardio-vascular diseases - Ogórek, Marlena Anna; Fidecki, Wiesław; Zarzycka, Danuta (Journal of Education, Health and Sport, 2018)
Abstract Introduction and purpose of the work Interest in health behaviors is particularly important in these groups of chronic diseases in which there is a significant morbidity and mortality of patients. This study is to determine the most frequently undertaken health behaviors among cardiac patients, and whether those behaviours depend on the sex. Material and method Study Design: Diagnostic study. Data were derived from respondents between 15th of April 2016 and 5th May 2016 in Independent Public Clinical Hospital No.4, 1st Military Hospital in Lublin, Cardiology Hospital in Nałęczów and Non-public Outpatients Clinic in Abramów. Results In this exploration 211 people took part, out of which the majority were female (59,2%). The most frequently taken by cardiac patients activities are conducive to health preventive behaviors (M = 3.63; SD = 0.81), a positive mental attitude (M = 3.59; SD = 0.72) and health practices (M = 3.54, SD = 0.75). The most common adverse health are conducive to the practice of health (M = 3.60; SD= 0.75), a positive mental attitude (M= 3.59; SD= 0.67) and preventive behaviours (M = 3 , 58; SD = 0.79). Conclusions Women received higher average severity of health behaviors than men. Engaging in healthy lifestyle behaviors was found to be positively associated with awareness of CHD.